2006
DOI: 10.1111/j.1365-2354.2005.00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Headache characteristics and brain metastases prediction in cancer patients

Abstract: The aim of this study was to evaluate the headache and other neurological symptoms and signs as guide predictors for the occurrence of brain metastases in cancer patients. We prospectively studied 54 cancer patients with newly appeared headache or with a change in the pattern of an existing headache during the recent months. All patients completed a questionnaire regarding headache's clinical characteristics and existence of accompanying symptoms. They also underwent a detailed neurological, ophthalmologic exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 15 publications
0
26
0
1
Order By: Relevance
“…They recommended MRI of the brain in all cancer patients with new or changed headache. Argyriou et al [14] also found that emesis and a bilateral frontotemporal headache with duration of 8 weeks or more, pulsating quality of the headache, and moderate to severe intensity were independent predictors of brain metastases as were gait instability and extensor plantar responses.…”
Section: Epidemiologymentioning
confidence: 96%
See 1 more Smart Citation
“…They recommended MRI of the brain in all cancer patients with new or changed headache. Argyriou et al [14] also found that emesis and a bilateral frontotemporal headache with duration of 8 weeks or more, pulsating quality of the headache, and moderate to severe intensity were independent predictors of brain metastases as were gait instability and extensor plantar responses.…”
Section: Epidemiologymentioning
confidence: 96%
“…These findings agree with Clouston et al [13], who reported that 32 of 97 cancer patients (33%) with undiagnosed headache had cerebral, leptomeningeal, or base of skull metastases. Argyriou et al [14] found that 29 of 54 (54%) cancer patients with new or changed headache had brain metastases. Many of these patients had additional symptoms or signs and could not be considered to have isolated headache.…”
Section: Epidemiologymentioning
confidence: 99%
“…These symptoms also relate to increased intracranial pressure. The headaches tend to be persistent and progressive, occurring more frequently with lengthening duration and increasing intensity (Argyriou et al, 2006;Jeyapalan & Batchelor, 2000;Yamanaka, Koga, Yamamoto, Sano, & Fukushige, 2011).…”
Section: Direct Complicationsmentioning
confidence: 99%
“…In the patient with known cancer, new onset or worsening of previous headache always merit neuroimaging, as metastases are found in up to 54% [9]. Prospective analysis of 68 patients with cancer with new headache revealed that AED antiepileptic drugs, CNS central nervous system, CSF cerebrospinal fluid, EBP epidural blood patch, ICP intracranial pressure, N/S none specified, NSAIDS nonsteroidal anti-inflammatory drugs, RPLS reversible posterior leukoencephalopathy syndrome, XRT radiotherapy duration of less than 10 weeks, emesis, and pain not of tension specificity were significant predictors of metastases [10].…”
Section: Introductionmentioning
confidence: 99%